Congenital nasal pyriform aperture stenosis with holoprosencephaly and Dandy–Walker malformation - Ismail, Intan Hakimah; Zainal Abidin, Mohd Azri (Wolters Kluwer Medknow Publications, 2020)
Congenital nasal pyriform aperture stenosis (CNPAS) is a recognized but rare and unusual cause of nasal airway obstruction in neonates. We describe an infant who has CNPAS with megaincisor, holoprosencephaly, agenesis of the corpus callosum with Dandy–Walker malformation, and central diabetes insipidus to highlight the importance of recognizing the variable abnormalities associated with this condition.